Three-year dynamics of left ventricular structural parameters in patients with resistant arterial hypertension on four-component therapy - О. О. Matova; L. A. Mishchenko; O. H. Kupchynska; K. I. Serbeniuk (Zaporožskij Medicinskij Žurnal)
Aim. To study the three-year dynamics of left ventricular (LV) structural parameters with the four-component antihypertensive therapy in patients with resistant arterial hypertension (RAH).